Mimochrome, a metalloporphyrin‐based catalytic Swiss knife. (19th July 2020) - Leone, Linda; Chino, Marco; Nastri, Flavia; Maglio, Ornella; Pavone, Vincenzo; Lombardi, Angela
Abstract: Over the years, mimochromes, a class of miniaturized porphyrin‐based metalloproteins, have proven to be reliable but still versatile scaffolds. After two decades from their birth, we retrospectively review our work in mimochrome design and engineering, which allowed us developing functional models. They act as electron‐transfer miniproteins or more elaborate artificial metalloenzymes, endowed with peroxidase, peroxygenase, and hydrogenase activities. Mimochromes represent simple yet functional synthetic models that respond to metal ion replacement and noncovalent modulation of the environment, similarly to natural heme‐proteins. More recently, we have demonstrated that the most active analogue retains its functionality when immobilized on nanomaterials and surfaces, thus affording bioconjugates, useful in sensing and catalysis. This review also briefly summarizes the most important contributions to heme‐protein design from leading groups in the field. Abstract : Similarly to a swiss knife, that bears a variety of tools stowed inside a single handle, Mimochromes are miniaturized hemeproteins, featuring a wide set of functions, fitted into a single molecular scaffold.